Platelet count and hypertension as indicators of height loss in the general population: A prospective study. - Yuji Shimizu; Hirotomo Yamanashi; Yuko Noguchi; Shin-Ya Kawashiri; Kazuhiko Arima; Yasuhiro Nagata; Takahiro Maeda (PLoS ONE)
Circulating CD34-positive cell count is inversely associated with height loss. It acts as an indicator of endothelial repair activity. In conjunction with CD34-positive cells, platelets contribute to endothelial repair. The presence of hypertension increases the demand for endothelial repair. Therefore, platelet count could be associated with height loss among individuals with hypertension. A retrospective study of 2,343 individuals aged 40 to 79 years was conducted. Height loss was defined as being in the highest quartile of annual height decrease (1.6 mm/year for men and 2.0 mm/year for women). A significant inverse association between platelet count and height loss was observed only among participants with hypertension. After adjusting for known cardiovascular risk factors, the odds ratio (95% confidence interval) for height loss per 1 standard deviation increment in platelet count (5.09×104/μL for men and 5.03×104/μL for women) was 0.83 (0.70, 0.98) for participants with hypertension and 1.02 (0.90, 1.16) for participants without hypertension. Independent of known cardiovascular risk factors, platelets could prevent accelerated height loss among individuals with hypertension. Unlike CD34-positive cell count, platelet count and blood pressure, which are easy to assess in daily clinical practice, influence height loss.